Developing Numeration Literacy Test Based on Bataknese Ethnomathematics in Three-Variable Linear Equation Lesson - Cut Nabilah Damni; Reflina Reflina (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
One of the factors contributing to the low ability to understand numeracy literacy is the lack of test instruments to improve numeracy literacy skills. Thus, test development is needed to improve students' numeracy literacy skills. A numeracy literacy instrument based on ethnomathematics is a test that is rarely learned at schools. This study aims to produce a qualified ethnomathematics-based numeracy literacy test. This research follows the Research and Development (R & D) method with a 4-D model. The data collection was carried out using a validation test instrument and test. This study produced 16 items of multiple-choice questions and 5 items of essays that were declared valid and suitable for use. The multiple-choice test is reliable with a coefficient of 0.738, an average differentiating power of 0.35 (good), and an average level of difficulty of 0.518 (medium) and distractors function well. The essay test instrument was declared reliable with a reliability coefficient of 0.942, an average differentiating power of 0.41 (good), and an average level of difficulty of 0.56 (medium). Based on tests of validity, different strengths, the level of hardness, and instrument practicality are obtained an average percentage of 82,91%% by students of a very practical category and 80% by teachers with a practical category. Thus it is gained that an assessment instrument developed is stated to be practical and suitable for use as an exercise instrument for developing student numeration literacy capability Keywords: test instrument, numeracy literacy, ethnomathematics.